Bioclimatology, biogeography and land use of Trás-os-Montes - Monteiro-Henriques, T. (2011)
Frequently climate is considered the first factor influencing flora, and consequently, vegetation distribution (Walter 1986; Woodward & B. G. Williams 1987; Capelo 2003; Peinado et al. 2007). Bioclimatology is the science that investigates the relationship between climate and the distribution of organisms. Rivas-Martínez’s Worldwide Bioclimatic Classification (RMWBC) has been developed by Rivas-Martínez with a number of approaches since 1982 (Rivas-Martínez 1996; 2008), with close reference to vegetation distribution, and is currently the most widely applied classification by Iberian phytosociologists, as well as from other Mediterranean countries. Based on the RMWBC, Monteiro-Henriques (2010) produced a set of bioclimatological maps for mainland Portugal (1960-1990) using the climatic statistical interpolations of Silva (2005) and Nicolau (2002) as base data. Using these bioclimatological maps of Monteiro-Henriques (2010) we present thermotype and ombrotype maps for mainland Portugal following the latest version of the RMWBC (Rivas-Martínez 2008), with particular focus on the Morais-Bragança area (Figure 5 and 6).